A modified firefly algorithm to maximize heat dissipation of a rectangular porous fin in heat exchangers exposed to both convective and radiative environment. (December 2019) - Deshamukhya, Tuhin; Nath, Ratnadeep; Hazarika, Saheera Azmi; Bhanja, Dipankar; Nath, Sujit
The current study deals with the optimization of significant parameters of aluminium and copper rectangular porous fins using firefly algorithm with reflective boundary condition. The study has been done considering convective heat transfer, in the first case, as well as combined convective and radiative modes of heat transfer, in the second case. To solve the non-linear governing equation, a semi analytical technique, differential transformation method is adopted. The results obtained by differential transformation method are validated by the numerical solution obtained by the finite difference method. The performance of firefly algorithm is evaluated by comparing with the results obtained by particle swarm optimization where it is seen that for the current set of equations, firefly algorithm took lesser number of iterations and computational time to converge than particle swarm optimization for all the cases. The analysis has been done for three different fin volumes and the effect of important variables which directly influence the heat transfer rate through porous fins has been discussed.